Creating synthetic spaces for higher-order topological sound transport - Hui Chen (Nature Portfolio, 2021)
The authors create synthetic dimensions in acoustic crystals composed of cavity arrays, strongly coupled through modulated channels. They provide evidence for 1D and 2D dynamic topological pumping, and show that the higher-order topological sound transport is robust against the geometrical imperfections.